Rivigo - Raghuram, G., active 1996; Sanghani, Pooja (London : Indian Institute of Management, Ahmedabad, 2017)
Rivigo was a new entrant in the trucking business in India. They believed that a new paradigm in the trucking/logistics industry could be brought about that would not only improve the quality of service dramatically, but also upgrade a truck driver's lifestyle. While the industry faced driver shortage largely due to long stays away from home, Rivigo hoped to attract drivers by offering them roles which would bring them back home in 24 hours. Drivers would be part of a relay, handing over the truck at pit stops. Further, they leveraged an IT-enabled IoT platform on a fleet of owned trucks. All this revolutionized most of the traditions then followed in the industry. The entrepreneur and his core team comprised professionals from premium institutes of the country, with experience in professional organizations in related domains. By offering services like assured delivery at half the time and full shipment visibility, Rivigo was able to charge a premium for the services and get acceptance from clients. The business model was able to attract significant funding from angel investors, debt funds, private equity investors and banks. The case raises the question of sustainability in the context of a USD 75 million minor equity stake by a private equity firm.
Originally Published InRaghuram, G. & Sanghani, P. (2017). Rivigo. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Rivigo -- Case studies; New business enterprises -- India -- Case studies; Trucking -- India -- Case studies; Truck drivers -- India -- Case studies; Strategic planning -- Case studies